Building quality into design process through digital human modelling. (2016) - Demirel, H. Onan; Duffy, Vincent G.
This paper represents modified virtual build methodology, which utilises digital human modelling as an approach to build quality into design process early in conceptualisation stage. Safety and reliability has utmost importance when it comes to total quality assurance. Ignoring or omitting safety and reliability aspects of human-product interactions not only result in poor market share, but also lead to injury and casualty. However, many industries still have the same challenge that products fail due to ignoring and/or omitting safety and reliability aspects of human-product interactions. Digital human modelling has the potential to integrate human capabilities, limitations and needs early into the product design process. This approach supports designers in minimising problems that could be detected and corrected earlier, which increase the likelihood of designing a safer and reliable product.